THE SCOPE AND NATURE OF ACTIVITIES OF THE ARMENIAN CHARITABLE SOCIETY OF BAKU - Stepanan, Gevorg Srapionovic; Ambarcuman, Naira Valerevna; Marukan, Armen Colakovic (History, Archeology and Ethnography of the Caucasus, 2025)
This study investigates the activities of the Armenian Charitable Society in the Baku Governorate and broader Transcaucasia during the second half of the 19th and early 20th centuries, focusing on its primary areas of operation. The research aims to systematize the activity of Armenian charitable societies, particularly the Baku Armenian Charitable Society, in relation to their objectives of preserving Armenian identity within Baku city and the Baku province. Furthermore, it examines the establishment and maintenance of the Society’s subsidiary institutions, including schools, hospitals, libraries, orphanages, nursing homes, and aid distribution points for the needy. These institutions were established and sustained through the philanthropic efforts of Armenian intellectuals and affluent individuals. Employing historical-analytical methods, this study draws upon a wide array of primary and secondary sources. These include the Acts of the Caucasian Archaeographic Commission, bulletins and activity reports of the Baku Armenian Charitable Society and its library’s reference materials, archival holdings from the National Archives of the Republic of Armenia, and extensive periodical press from the Society’s period of activity. Additionally, the research incorporates relevant monographs, scholarly articles, and contemporary accounts. The findings indicate that the Baku Armenian Charitable Society played a crucial role in safeguarding the identity and promoting the overall development of Armenians within Baku province. The Society engaged in cultural and educational initiatives among the Armenian population, provided financial support to Armenian writers, artists, teachers, orphans, widows, disaster victims, and refugees. It also offered scholarships to Armenian students attending European and Russian universities, as well as those at the Tiflis Nersisyan School and the Echmiadzin Gevorgyan Lyceum. The activities of the Baku Armenian Charitable Society concluded in May 1920.